2020
DOI: 10.1186/s13020-020-00356-4
|View full text |Cite
|
Sign up to set email alerts
|

Herb–drug interactions between the medicinal mushrooms Lingzhi and Yunzhi and cytotoxic anticancer drugs: a systematic review

Abstract: Background: Lingzhi and Yunzhi are medicinal mushrooms commonly used with cytotoxic chemotherapy in cancer patients in Asian countries. The current systematic review aims to identify potential pharmacokinetic or pharmacodynamic interactions from the existing literature to ensure their effective and safe combination usage in cancer patients. Methods: A systematic search was conducted on nine major Chinese and English databases, including China Journal Net, Allied and Complementary Medicine Database, and Ovid ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 95 publications
0
7
0
Order By: Relevance
“…In particular, two medicinal mushrooms belonging to Polyporaceae , namely lingzhi (reishi) and yunzhi, are used as adjuvants in cancer therapy not only in the East but also in Canada, the United States, and Europe. At the clinical level, yunzhi is coadministered with ACDs such as 5 FU, tegafur/uracil, and mitomycin, while linghzi is coadministered with cisplatin, paclitaxel, and 5 FU in most of the clinical trials that were analyzed [ 35 ]. From the analysis of 77 clinical trials, combining these two fungi with ACDs could improve the survival rates and HR -QoL of patients under cancer treatment [ 35 ].…”
Section: Drug–herbal-product Association: Effects On Pharmacokinetics...mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, two medicinal mushrooms belonging to Polyporaceae , namely lingzhi (reishi) and yunzhi, are used as adjuvants in cancer therapy not only in the East but also in Canada, the United States, and Europe. At the clinical level, yunzhi is coadministered with ACDs such as 5 FU, tegafur/uracil, and mitomycin, while linghzi is coadministered with cisplatin, paclitaxel, and 5 FU in most of the clinical trials that were analyzed [ 35 ]. From the analysis of 77 clinical trials, combining these two fungi with ACDs could improve the survival rates and HR -QoL of patients under cancer treatment [ 35 ].…”
Section: Drug–herbal-product Association: Effects On Pharmacokinetics...mentioning
confidence: 99%
“…Table 3 [ 7 , 8 , 9 , 16 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] lists the best-known, studied, and used CAMs whose main recognized role is to improve HR-QoL, although there is conflicting evidence that CAM improves HR-QoL and symptoms [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the causes of cancer are multifactorial, and they include genetic, environmental, and other risk factors. A recent meta-analysis of 213 studies, including 77 clinical studies, showed that Ganoderma lucidum or Coriolus versicolor mushrooms enhanced the efficacy and ameliorated their adverse effects, which lead to an improved quality of life in cancer patients [108,167].…”
Section: Antitumour Activity Of Mushroomsmentioning
confidence: 99%
“…The herb-pair has their inherent prescriptions and it is a bridge between single herb and prescriptions. Traditional Chinese medicine (TCM)-herbal mixtures developed though observation and experience accumulated over thousands of years, but with unknown mechanisms of action [9].…”
Section: Introductionmentioning
confidence: 99%